Analisis Faktor Penyebab Keterlambatan Pengembalian Rekam Medis Pasien Rawat Inap di RSUD Kudungga - Juwinda Indriyani; Atma Deharja; Rossalina Adi Wijayanti; Gamasiano Alfiansyah (Manajemen Pelayanan Kesehatan, 2024)
The delay in returning inpatient medical records at RSUD Kudungga in East Kutai Regency is 94.33%, well below the standard of 100% within 48 hours after patient discharge. This is mainly due to the inpatient admins’ untimely behavior in returning the records. This study aims to analyze the factors causing the delay in returning inpatient medical records at RSUD Kudungga. The qualitative research collected data through interviews, observations, documentation, and brainstorming. Data validity was tested using source and technique triangulation. The analysis revealed several causes for the delay. Predisposing factors include a lack of awareness among inpatient admins about timely returns. Enabling factors involve the absence of trolleys for transporting records, the significant distance between inpatient rooms and the records room, and inadequate training for admins. Reinforcing factors include a lack of motivation in the form of praise and punishment for staff, and the absence of evaluations of the SOP for returning records. Improvement efforts include routine evaluations of staff, provision of trolleys, admin training, motivation incentives, and monitoring and evaluating the SOP for returning inpatient medical records.